Identifikasi Faktor-Faktor yang Menentukan Status Keberlanjutan Usaha Tempat Penampungan dan Potong Ayam (TPnA) di Wilayah Pondok Rumput Kota Bogor - Luh Putu Desy Puspaningrat; Eko Sugeng Prihadi; Maya Dewi Dyah Maharani (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Increased broiler production in Bogor Regency leads to the continuous development of traditional chicken collecting facilities and slaughterhouse (CCFS), especially in Bogor City. Pondok Rumput area, located in Kebon Pedes Village, as one of CCFS centers. Pondok Rumput CCFS was first established in 1971. There are currently 25 CCFS in Pondok Rumput. The CCFS in this area are located in densely populated residential area. The CCFS, are located in the middle of the residential area leads to various problems, one of which is environmental pollution.The Study aimed to identify the factors determining the sustainability status of CCFS in Pondok Rumput area, in Tanah Sareal Subdistric, Bogor City. The types of data collected included primary and secondary data. The data analysis used by Multi Dimensional Scalling (MDS) analysis (by using Rapfish software) and prospective analysis. Partial analysis of each dimension concerning the sustainability status of chicken collecting facilities and slaughterhouse in Pondok Rumput showed that ecological dimension were not unsustainable with a value of 24.66. The key attributes were having business license, conformity to slaughtering regulations, entrepreneurs’ attitudes towards relocation, and business feasibility.